Control Implementation in Bioprocess System: A Review. - Zulkeflee, S.A; Aziz, N. (2007)

(untitled)
Bioprocess control consists of establishing a strategy for the management of the biocatalyst environment. Bioprocesses include several different units in which a near optimal environment is desired for microorganisms to grow, multiply, and produce a desired product.